PENGUKURAN KUALITAS LAYANAN PADA BISNIS JASA - Yasrizal Yasrizal (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2017)
ABSTRAKThe global economy today has encouraged the growth of rapidly growing service business. Many jobscan be developed, such as healthcare, hospitality, service station, fast food, laundry,telecommunications, and others. The presence of a variety of business services has sparked fiercecompetition among service businesses. To anticipate this service managers should seek to provide or payattention to the quality of services offered, so that consumers are satisfied. To maintain the quality ofservice always remains good, the service managers need to pay attention to dimensions-dimensionalmeasurement of service quality. By measuring the quality of services, the manager informed about theextent of services provided has to meet consumer expectations.Keyword:service quality , performance score, services provided, Hopes services